Heterotopias : Nationalism and the possibility of history in South Asia - Bhagavan, Manu; Bhagavan, Manu Belur, 1970- (New Delhi : Oxford University Press, 2010)
Papers presented at a conference held at Indian University in February 2003.
Includes bibliographical references.
Keywords: Nationalism in literature -- Congresses